TNF-α-Induced cPLA2 Expression via NADPH Oxidase/Reactive Oxygen Species-Dependent NF-κB Cascade on Human Pulmonary Alveolar Epithelial Cells - Lin, Chih-Chung; Lin, Wei-Ning; Cho, Rou-Ling; Wang, Chen-yu; Hsiao, Li-Der; Yang, Chuen-Mao (Frontiers in Pharmacology, 2016)
Tumor necrosis factor-alpha (TNF-alpha) triggers activation of cytosolic phospholipase A2 (cPLA2) and then enhancing the synthesis of prostaglandin (PG) in inflammatory diseases. However, the detailed mechanisms of TNF-alpha induced cPLA2 expression were not fully defined in human pulmonary alveolar epithelial cells (HPAEpiCs). We found that TNF-alpha-stimulated increases in cPLA2 mRNA (5.2 folds) and protein (3.9 folds) expression, promoter activity (4.3 folds), and PGE2 secretion (4.7 folds) in HPAEpiCs, determined by Western blot, real-time PCR, promoter activity assay and PGE2 ELISA kit. These TNF-alpha-mediated responses were abrogated by the inhibitors of NADPH oxidase [apocynin (APO) and diphenyleneiodonium chloride (DPI)], ROS [N-acetyl cysteine, (NAC)], NF-kappaB (Bay11-7082) and transfection with siRNA of ASK1, p47phox, TRAF2, NIK, IKKalpha, IKKbeta, or p65. TNF-alpha markedly stimulated NADPH oxidase activation and ROS including superoxide and hydrogen peroxide production which were inhibited by pretreatment with a TNFR1 neutralizing antibody, APO, DPI or transfection with siRNA of TRAF2, ASK1, or p47phox. In addition, TNF-alpha also stimulated p47phox phosphorylation and translocation in a time-dependent manner. On the other hand, TNF-alpha induced TNFR1, TRAF2, ASK1, and p47phox complex formation in HPAEpiCs, which were attenuated by a TNF-alpha neutralizing antibody. We found that pretreatment with NAC, DPI, or APO also attenuated the TNF-alpha-stimulated IKKalpha/beta and NF-kappaB p65 phosphorylation, NF-kappaB (p65) translocation, and NF-kappaB promoter activity in HPAEpiCs. Finally, we observed that TNF-alpha-stimulated NADPH oxidase activation and ROS generation activates NF-kappaB through the NIK/IKKalpha/beta pathway. Taken together, our results demonstrated that in HPAEpiCs, up-regulation of cPLA2 by TNF-alpha is, at least in part, mediated through the cooperation of TNFR1, TRAF2, ASK1, and NADPH oxidase leading to ROS generation and ultimately activates NF-kappaB pathway.